YTHDF3 mediates HNF1α regulation of cervical cancer radio‐resistance by promoting RAD51D translation in an m6A‐dependent manner. (15th December 2022) - Du, Hui; Zou, Nai‐Yi; Zuo, Hong‐Ling; Zhang, Xue‐Yuan; Zhu, Shu‐Chai
Abstract : Radiotherapy, as an important primary treatment, has effectively improved the survival of patients with cervical cancer (CC). Some patients, however, do not benefit optimally from radiotherapy because of radio‐resistance. Therefore, identifying radio‐resistance biomarkers and unravelling the underlying mechanisms is of critical importance for these patients. In the present study, we found significant upregulation of hepatocyte nuclear factor 1‐alpha (HNF1α) expression in radio‐resistant cervical cancer tissues and cell lines. Depletion of HNF1α reduced and overexpression of HNF1α promoted the resistance of CC cells to irradiation in vitro and in vivo . HNF1α positively regulated DNA repair protein RAD51 homologue 4 (RAD51D) at the protein level but not at the mRNA level. Mechanistically, upregulation of HNF1α enhanced YTH domain‐containing family protein 3 (YTHDF3) transcription, which in turn promoted RAD51D mRNA N 6 ‐methyladenosine (m6A) modification. YTHDF3 mediates HNF1α regulation of cervical cancer radio‐resistance by promoting RAD51D translation in an m6A‐dependent manner. The HFN1α/YTHDF3/RAD51D regulatory axis was found to play a critical role in conferring radio‐resistance of CC cells. In conclusion, dysregulation of the HFN1α/YTHDF3/RAD51D axis may promote the radio‐resistance of CC cells. Blocking this pathway may provide therapeutic benefits against CC radio‐resistance. Abstract : We found that the expression of hepatocyte nuclear factor 1‐alpha (HNF1α) was upregulated in radio‐resistant cervical cancer (CC) tissues and cell lines. Depletion of HNF1α reduced and overexpression of HNF1α promoted the resistance of CC cells to irradiation in vitro and in vivo . The upregulation of HNF1α enhanced YTH domain‐containing family protein 3 (YTHDF3) transcription, which in turn promoted RAD51 homologue 4 (RAD51D) mRNA N 6 ‐methyladenosine (m6A) modification. YTHDF3 mediates HNF1α regulation of cervical cancer radio‐resistance by promoting RAD51D translation in an m6A‐dependent manner.